2020
DOI: 10.1177/1093526620957219
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lung Cribriform Adenocarcinoma With Squamoid Morules Harboring Somatic CTNNB1 Mutation in a Never-Smoked Healthy Adolescent

Abstract: Primary lung adenocarcinomas are rare in pediatric patients, and even rarer in patients without precedent malignancy or congenital malformation. Here we present the first reported case of primary lung cribriform adenocarcinoma with squamoid morules in a previously healthy adolescent female. Molecular testing identified CTNNB1 mutation in the tumor and excluded other common mutations in lung adenocarcinoma. Our case suggests molecular alterations to the same signaling pathway can lead to similar histomorphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…D.Barggio et al [100], demonstrated the apoptotic resistance of desmoid cells that harbor the p.SF45F β-catenin mutation with a downregulation of the RUNX3 protein expression. CTNNB1 mutations may result to rare cases, such as the case report of a never-smoked adolescent with a healthy family history diagnosed as the first reported pediatric case with lung aede-nocarcinomas, where the molecular testing and sequencing panels found that CTNNB1 mutation is the only alteration in the 17 years old patient [101].…”
Section: Uncommon Cancer Variants With Important Clinical Impact Are ...mentioning
confidence: 99%
“…D.Barggio et al [100], demonstrated the apoptotic resistance of desmoid cells that harbor the p.SF45F β-catenin mutation with a downregulation of the RUNX3 protein expression. CTNNB1 mutations may result to rare cases, such as the case report of a never-smoked adolescent with a healthy family history diagnosed as the first reported pediatric case with lung aede-nocarcinomas, where the molecular testing and sequencing panels found that CTNNB1 mutation is the only alteration in the 17 years old patient [101].…”
Section: Uncommon Cancer Variants With Important Clinical Impact Are ...mentioning
confidence: 99%